Distinct Response to Platinum-Based Chemotherapy among Patients with Metastatic Castration-Resistant Prostate Cancer Harboring Alterations in Genes Involved in Homologous Recombination. Issue 3 (27th September 2021) - Fan, Liancheng; Fei, Xiaochen; Zhu, Yinjie; Chi, Chenfei; Pan, Jiahua; Sha, Jianjun; Xin, Zhixiang; Gong, Yiming; Du, Xinxing; Wang, Yanqing; Dong, Baijun; Xue, Wei
Abstract : Purpose: We aimed to explore the association between genomic status and clinical outcome of platinum-based chemotherapy among patients with metastatic castration-resistant prostate cancer (mCRPC). Materials and Methods: We conducted a retrospective study of 55 patients with mCRPC who received platinum-based chemotherapy after the progression to docetaxel chemotherapy and underwent genomic profiling of 14 homologous recombination (HR) pathway genes. Progression-free survival (PFS) was analyzed using the Kaplan-Meier method. Results: Of 55 patients, 23 harbored genomic defects in HR pathway genes. Median prostate specific antigen (PSA)-PFS for the HR defect group was 6.7 months compared with 2.6 months for the no HR defect group (p=0.001). The patients harboring somatic HR defect displayed shorter PSA-PFS than those harboring germline HR defect (4.5 months vs not available; p=0.066). The PSA50 (patients who survived for 12 weeks and had a PSA decline over 50% from baseline) response rate displayed higher in patients harboring BRCA2 or ATM defect (6/8, 75.0%) than in those harboring CDK12 defect (2/9, 22.2%; p=0.06). Patients harboring BRCA2 or ATM defect displayed prolonged PSA-PFS, compared with those harboring CDK12 defect and those harboring other HR defect (p=0.038). In multivariate Cox regression analysis, HR defect and BRCA2 or ATM defect were independent significant factors associated with superior PAS-PFS to platinum-based chemotherapy. Conclusions: The patients with mCRPC harboring alterations in different HR genes displayed distinct response to platinum-based chemotherapy. Patients with mCRPC harboring genomic defects in crucial HR genes either in the germline or somatic, especially BRCA2 and ATM, might experience superior outcomes to platinum-based chemotherapy, compared with those harboring CDK12 defect.